Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity